Numerical Studies of Batch and Inline High Shear Melt Conditioning Technology Using Different Rotors - Gerard Serge Bruno Lebon; Jayesh B. Patel; Zhongyun Fan (Crystals, 2022)
When casting aluminum alloy billets, high shear melt conditioning (HSMC) technology refines the resulting grain size, reduces the number of defects, and improves mechanical properties without the need to add polluting and expensive chemical grain refiners. These resultant improvements spring from the high shear rates that develop in the rotor–stator gap and the stator holes facing the leading edge of the rotor. Despite the growing literature on rotor–stator mixing, it is unclear how the different rotor–stator parameters affect the performance of high shear treatment. To upscale this technology and apply it to processes that involve large melt volumes, an understanding of the performance of the rotor–stator design is crucial. In this paper, we present the results of computational fluid dynamics (CFD) studies of high shear melt conditioning in continuous and batch modes with different rotor designs. These studies build upon our earlier work by studying the effect of rotor variation in a stator design consisting of rows of small apertures at different rotor speeds spanning from 1000 to 10,000 revolutions per minute. While no clear-cut linear pattern emerges for the rotor performance (as a function of the design parameters), the rotor geometry is found to affect the distributive mixing of microparticles, but it is insignificant with regards to their disintegration.